Human MCTS1-dependent translation of JAK2 is essential for IFN-γ immunity to mycobacteria - Bohlen, Jonathan; Zhou, Qinhua; Philippot, Quentin; Ogishi, Masato; Rinchai, Darawan; Nieminen, Tea; Seyedpour, Simin; Parvaneh, Nima; Rezaei, Nima; Yazdanpanah, Niloufar; Momenilandi, Mana; Conil, Clément; et al. (Cell, 2023)
Human inherited disorders of interferon-gamma (IFN-γ) immunity underlie severe mycobacterial diseases. We report X-linked recessive MCTS1 deficiency in men with mycobacterial disease from kindreds of different ancestries (from China, Finland, Iran, and Saudi Arabia). Complete deficiency of this translation re-initiation factor impairs the translation of a subset of proteins, including the kinase JAK2 in all cell types tested, including T lymphocytes and phagocytes. JAK2 expression is sufficiently low to impair cellular responses to interleukin-23 (IL-23) and partially IL-12, but not other JAK2-dependent cytokines. Defective responses to IL-23 preferentially impair the production of IFN-γ by innate-like adaptive mucosal-associated invariant T cells (MAIT) and γδ T lymphocytes upon mycobacterial challenge. Surprisingly, the lack of MCTS1-dependent translation re-initiation and ribosome recycling seems to be otherwise physiologically redundant in these patients. These findings suggest that X-linked recessive human MCTS1 deficiency underlies isolated mycobacterial disease by impairing JAK2 translation in innate-like adaptive T lymphocytes, thereby impairing the IL-23-dependent induction of IFN-γ.
Online verfügbar: 23. Oktober 2023
Gesehen am 09.02.2024